Implementasi Program Satu Nagari Satu Event (SNSE) Sebagai Program Unggulan Pemerintah Kabupaten Tanah Datar dalam Melestarikan Kebudayaan Lokal - Rahmadya Aydini; Rizki Syafril (Asosiasi Ilmuwan Administrasi Negara (ASIAN), 2024)
This research aims to analyze the implementation of the One Nagari One Event (SNSE) policy in the Tanah Datar Regency. The background to this research is that SNSE is the flagship program of the Tanah Datar Regency government in preserving local Nagari culture. Currently, the regional government's flagship program SNSE has not been implemented by all nagari in Tanah Datar Regency. This program will be implemented starting in 2022 based on the Regency Regional Regulation Tanah Datar No.22 Th. 2022 dated July 15 2022 concerning Roadmap for Implementation of Featured Programs in the 2021-2026 Regional Medium Term Development Plan. In this research, researchers used a qualitative approach with descriptive methods. The data obtained was collected through the process of interviews, observation and documentation. The results of the research show that the implementation of the SNSE program as the flagship program of the Tanah Datar Regency government in preserving local Nagari culture has not been optimal because not all Nagari in Tanah Datar Regency have implemented this program; furthermore, this program does not stop at Nagari in Tanah Datar Regency only but will be judged, and the best Nagari will be displayed at the peak event at the end of the year, namely the Minangkabau Enchantment Festival.